ANALISIS PENERAPAN SIKLUS AKUNTANSI PADA USAHA MIKRO KECIL DAN MENEGAH KABUPATEN KERINCI: (Studi Kasus UMKM Dodol Kentang Di Lubuk Nagodang) TAHUN 2022 - Maryanto, Maryanto (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Small and Medium Enterprises (SMEs) are small business units that can play a role and function as a safety valve both in providing alternative productive business activities, alternative credit distribution, and in terms of employment. The problems that are often faced by MSME actors include product marketing, financial limitations, limited human resources, lack of raw materials, technological limitations, to financial management. Financial management through the application of the accounting cycle is sometimes neglected by SMEs. This study aims to determine the application of the accounting cycle carried out in UKM Dodol Kentang in Kerinci Regency in producing financial reports. This study uses a survey method that takes samples from the population using a questionnaire. The survey was conducted in Kerinci Regency, with 30 MSME respondents using descriptive analysis as an analytical tool. This study produces a weighted score of 0.6 which refers to the Guttman scale. This number is at a low rate of 0.00 to 0.25, there is no association or association (weak association), which indicates that SMEs in Purworejo Regency do not apply the accounting cycle to financial management. company. their business.